Intergraded Applied Methodology for the Treatment of Heavy Polluted Waste Waters from Olive Oil Industries - Antonis A. Zorpas; Vassilis J. Inglezakis (Applied and Environmental Soil Science)
The annual olive oil production in Cyprus is in the range of 2700–3100 t y−1, resulting in the generation of significant amount of waste. The cocomposting of the olive oil solid residue (OOSR) and the treated wastewaters (with Fenton) from the olive oil production process with the application of reed beds has been studied as an integrated method for the treatment of wastewater containing high organic and toxic pollutants under warm climate conditions. The experimental results indicated that the olive mill wastewater (OMW) is detoxified at the end of the Fenton process. Specifically, COD is reduced up to 65% (minimum 54.32%) by the application of Fenton and another 10–28% by the application of red beds as a third stage. The final cocomposted material of OOSR with the treated olive mile wastewater (TOMW) presents optimum characteristics and is suitable for agricultural purpose.